Re-politicising Anti-Trafficking: Migration, labour, and the war in Ukraine - Mendel, Jonathan; Sharapov, Kiril (Anti-Trafficking Review, 2024)
Drawing on multi-method research, this article demonstrates that the risks of large-scale trafficking due to the war in Ukraine were mitigated by granting Ukrainians more extensive rights than typically afforded to refugees. This shows the advantages of rights-based approaches to migration and labour exploitation. We draw on Bakhtin’s and Žižek’s work on the carnivalesque to argue that mainstream anti-trafficking initiatives—which are depoliticised and able to win support and funding from across the political spectrum—often serve merely as theatrical and distracting sideshows diverting attention from more impactful activities and the normalised exploitation within capitalism. However, avoiding trafficking is insufficient if Ukrainian citizens and residents still endure exploitative conditions. A weakened legal framework for workers’ rights within Ukraine alongside inadequate labour protections across Europe have facilitated such exploitation. In contrast to the depoliticised stance of the anti-trafficking industry, this article concludes that more explicitly political actions supporting migrants’ rights, workers’ rights, and access to welfare and public services will not only more effectively challenge trafficking but also prevent other exploitation of migrants.